Exchange networks from close-up: The case of Lipari obsidian (Journal of Lithic Studies, 2016)
A systematic study on obsidian tools in Calabria and Sicily carried out by the authors have revealed the uniqueness in the patterns of production, exchange and consumption of Lipari obsidian. The study has concentrated on the Middle Neolithic primarily, with other Neolithic and Bronze Age contexts recognised at a later stage in the research since many contexts, especially in Sicily, have been excavated by pioneering archaeologists, some over a century ago, or were mislabelled. The chronology is Early Neolithic to Early Bronze Age, with very few materials dating Middle Bronze Age. A review of chronological contexts is in progress, which spans from the 6th millennium BC to the end of the 2nd millennium BC. The typology of obsidian tools is very homogenous, the vast majority of used tools are small blades, bladelets and sharp flakes; there is negligible variance across time; and Lipari obsidian is preferred over other sources. The patterns of the exchanges are also unique, revealing two major types of redistribution of obsidian, one particularly intriguing because it is quite organized with a single source in Lipari, prominent and reminiscent for its stability and reach of Bronze Age redistribution dynamics associated with hierarchical societies. We present here some observations on patterns substantiated by the archaeological record, and consider possible scenarios that can explain them. This work provides an update on progressing research and reveals aspects that will need further investigation, focusing on the patterns identified so far and possible explanations. More work is certainly needed to produce a working model, but the unusual patterns deserve some attention on their own, unencumbered by an overarching explanatory model. In particular, we want to assess the Neolithic redistribution pattern suggestive as typical of hierarchical polities, and contextualize it to the specific situation of Neolithic Lipari.